PENERAPAN HUKUM ACARA PENGADILAN NIAGA YANG BERADA DALAM LINGKUP PERADILAN UMUM - Ladju Kusmawardi; Kholis Roisah (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
The Commercial Court is a special court within the General Courts. ThisCommercial Court has the authority to accept, examine and adjudicate the case foran application for bankruptcy statements, request for a delay in the obligation to paydebts (PKPU), other claims and intellectual property rights (IPR).This study aims todetermine the scope of duties and authority of the Commercial Court, the legalstanding of Creditors and Debtors after the dispute has been decided by HakimNiaga and has permanent legal force and the implementation of the execution at theCommercial Court. The approach method used in this research is sociologicaljuridical with the Semarang City research area, especially the SemarangCommercial Court. The research subjects included those involved in the proceedingsat the Semarang Commercial Court. Primary data and secondary data are obtainedthrough field surveys and literature studies.Based on the research and analysisresults, it is known that the scope of duties and authority of the Commercial Court isto accept, examine and decide on the case for an application for bankruptcystatements, postponement of the obligation to pay debts (PKPU), other claims andcases included in the field of intellectual property rights (IPR).The legal standing ofthe parties is that for the Debtor after being declared bankrupt by the CommercialCourt Judge, he loses the right to manage the bankrupt assets owned by him, but theDebtor's civil rights as a person (personrechi) is not lost.Regarding the execution ofthe Commercial Court that is still guided by the provisions of HI R / RBg as theexecution of civil cases in the District Court, this is because Law No. 4 of 1998 hasnot been regulated separately. Especially for the execution of the forged Brand case,the mark of the falsified goods / products is carried out at the Directorate General ofTrademark, Copy and Patent of the Ministry of Justice and Human Rights in Jakarta